Occurrence, distribution and activity of alkaline phosphatase producing bacteria in freshwater fishpond ecosystems - Barik, S K; Purushothaman, C S (Indian Journal of Fisheries, 2011)
In the freshwater fish ponds, Bacillus spp. were found to be the dominant bacteriaproducing phosphatase. The alkaline phosphatase activity of sediment was alwayshigher than that of water. In the case of water, though the 'dissolved' alkalinephosphatase activity was lower than the 'total' alkaline phosphatase activity, theformer was nevertheless unimportant as it constituted about 20% of the 'total'activity.